Modern Computer Vision with PyTorch : Explore deep learning concepts and implement over 50 real-world image applications /: Explore deep learning concepts and implement over 50 real-world image applications. (2020) - Ayyadevara, V Kishore; Reddy, Yeshwanth
No abstract available